Effect of temperature on mortars with incorporation of phase change materials - Cunha, Sandra Raquel Leite (2015)
Mortars with incorporation of phase change materials (PCM) have the ability to regulate the temperature inside buildings, contributing to the thermal comfort and reducing the use of heating and cooling equipment. However, it is important that they present a good behavior when subjected to aggressive conditions. The main purpose of this study was the effect of high temperatures on mortars with PCM. It was observed that the exposure to high temperatures leads to a decrease in the flexural, compressive and adhesion strengths. However, the behavior of the mortar with PCM is similar to reference mortars.